LE TERRITOIRE DE RUNGU FACE AUX DEFIS D’UNE ADMINISTRATION DU DEVELOPPEMENT - IKABU, Corneille BOGOY (IJRDO - Journal of Social Science and Humanities Research, 2020)
The present study shows the deficiencies of the public administration in the territory of Rungu in Democratic Republic of Congo, these deficiences require the establishment an administration of development.                        Illustratively,the amount of civil servants actually working, is estimated at 40,2%, in one hand, to this amount is added the average of 67,2% of agents ready for the retirement.                         For this reflexion, the imperatives of an administration of developpement in the territory of Rungu lie on the administrative management oriented towards results by motivating man, the latter being the principal actor of the development.